Peri-intubation adverse events and clinical outcomes in emergency department patients: the BARCO study - Maia, Ian Ward A.; Besen, Bruno A. M. Pinheiro; Silva, Lucas Oliveira J. e; von Hellmann, Rafael; Hajjar, Ludhmila Abrahao; Sandefur, Benjamin J.; Pedrollo, Daniel Fontana; Nogueira, Caio Goncalves; Figueiredo, Natalia Mansur P.; Miranda, Carlos Henrique; Martins, Danilo [UNESP]; Baumgratz, Thiago Dias [UNESP]; et al. (Springer Nature, 2025)
BackgroundEmergency tracheal intubation in critically ill patients carries a high risk of complications, and practices vary substantially across different settings. Identifying risk factors and understanding how peri-intubation adverse events affect patient outcomes may guide standardization of care and improve survival.MethodsThis prospective cohort study involved 18 emergency departments in Brazil (March 2022–April 2024). We included adults (≥ 18 years) undergoing emergency intubation and excluded patients intubated electively or for cardiac arrest. We defined major peri-intubation adverse events as severe hypoxemia, new hemodynamic instability, or cardiac arrest occurring within 30 min of initiating intubation. The primary outcome was 28-day mortality. Multivariable regression analyses assessed associations between adverse events and mortality, controlling for potential confounders.ResultsAmong 2846 patients, major adverse events occurred in 919 (32.3%) intubations, most frequently new hemodynamic instability (20.0%), followed by severe hypoxemia (12.5%) and cardiac arrest (3.5%). The overall 28-day mortality was 45.1%. Patients experiencing any major adverse event had a significantly higher 28-day mortality (57.6 vs 39.2%; aHR 1.43, 95% CI 1.26–1.62; p < 0.001). Sensitivity analyses confirmed these findings. Successful first-attempt intubation was associated with a reduced likelihood of major adverse events (aOR 0.52; 95% CI 0.41–0.65; p < 0.001).ConclusionOne in three patients undergoing emergency intubation experienced a major peri-intubation adverse event, which was associated with higher 28-day mortality. These results underscore the importance of optimizing intubation strategies to reduce complications and potentially improve patient outcomes in critically ill patients.